If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2k + k + 4 = 0 Reorder the terms: 4 + 2k + k = 0 Combine like terms: 2k + k = 3k 4 + 3k = 0 Solving 4 + 3k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3k = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 3k = 0 + -4 3k = 0 + -4 Combine like terms: 0 + -4 = -4 3k = -4 Divide each side by '3'. k = -1.333333333 Simplifying k = -1.333333333
| [t+5]+3=12 | | 7-2x=0 | | 6x+8=4x+50 | | 3x+8=8+2x+x | | 729=x^3 | | 4(d-20)=1 | | 245=-7a | | (36-5x)+(36-5x)+4x+4x=x | | 3x+28=7(x+4)-4x | | 2(6+3)=18-3(16-3d) | | 6+12=16 | | x+17=36-x | | x=20-0.5y | | 5=1-2n+5 | | 4(d-5)=1 | | 5m-14=8m+4 | | 2.5x-(-8.2)=26.7 | | -8n+4(1+5)=6n-14 | | -11(x+9)=99 | | 6x^4*3x^4= | | y=-0.80(55)+136 | | 4.3*p=28.81 | | 5n-9=71 | | 5(x+4)=75 | | 6y-7=10y+25 | | y=-0.80(45)+136 | | 7(1y+-2)+8=3(1y+-4)+-2 | | y=-0.80(35)+136 | | -18-6k=6(13k) | | 2x-1=-x+5 | | 15x^3-7x-2= | | x+29=83 |